Pulling up or binding down: A review of upgrading trajectories in apparel and agroprocessing global value chains for developing countries - Giovanni Pasquali; Aarti Krishnan; Jakob Engel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
There exist a plethora of developing country value chain studies based on a variety of methodological approaches, both in the academic literature and through policy reports. However, there has been little systematic synthesis of the findings and approaches taken in these studies. This study presents the results of a meta-analysis of 35 case studies (including 12 policy reports from the World Bank and 23 academic articles) on the determinants and outcomes of integration in apparel and agro-processing global value chains (GVCs) for primarily low-income developing countries. It explores the determinants of backward and forward participation in GVCs, and the factors that enable firms to achieve economic, social, and environmental upgrading. Furthermore, the study draws a connection between the causes and consequences of upgrading, shedding light on the economic, social, and environmental outcomes of the participation of firms in GVCs. Overall, this study aims to contribute to ongoing efforts to better understand how GVC analysis can inform economic transformation and job creation especially in low-income countries.
Keywords: E2; G10; L2; Q11; 330; global value chains; upgrading; apparel; agro-processing; low-income countries